Endoscopic Removal of Multiple Ballpoint Pens from the Stomach in a Patient with PICA - Islam, Mohammad Aminul; Islam, Md. Jahidul; Islam, Homayara; Sajib, Mohammad Waliul Hasnat (Archives of Clinical and Medical Case Reports, 2024)
The deliberate ingestion of foreign objects by adults is rare and necessitates immediate medical attention for diagnosis and treatment. We present a unique case of a 31-year-old male with mental retardation and a history of drug abuse who sought medical attention due to abdominal pain. Radiological investigations (X-rays) established the presence of multiple pointed metallic objects within his stomach, later identified as ballpoint pens through an endoscopic view. The patient underwent two successful endoscopic interventions, resulting in the removal of 23 ballpoint pens. No adverse effects were recorded during the post-procedure follow-up period. The patient's underlying condition, PICA, was addressed through a combination of psychiatric treatment with medication psychiatric therapies and multidisciplinary care.